Role of aspirin, beta-blocker, statins, and heparin therapy in septic patients under mechanical ventilation: a narrative review - Al-Husinat, Lou'i; Abu Hmaid, Amer; Abbas, Hadeel; Abuelsamen, Batool; Albelbisi, Mutaz; Haddad, Said; Qamileh, Ibrahim; Quneis, Ossaid; Al Modanat, Zaid Jehad; Ferrara, Giuseppe; Dias, Fernando Suparregui; Cinnella, Gilda (Frontiers in Medicine, 2023)
Sepsis is the main cause of death among patients admitted to intensive care units. Management of sepsis includes fluid resuscitation, vasopressors, intravenous antimicrobials, source control, mechanical ventilation, and others. New insights into the potential benefits of non-antimicrobial drugs in sepsis have evolved, but the findings are still controversial. In this narrative review, we aim to evaluate effect of beta-blockers, aspirin, statins, and heparin as adjunctive treatments on mortality in septic patients under mechanical ventilation with non-cardiovascular diseases. We searched PubMed with relevant keywords (beta-blockers, aspirin, statin, or heparin, and critically ill or sepsis) for the last 10 years and some personal collection of relevant articles, then we assessed studies according to prespecified inclusion and exclusion criteria. Our results show that beta blockers, aspirin, and heparin may have promising feedback on reducing mortality but still new well controlled, randomized, multicenter studies are needed to confirm this, and multiple issues regarding their usage need to be addressed. Statins feedback wasn't as good as others but we suggest further studies to confirm these results.